Analisis Hasil Radiografi Os Clavicula Pada Proyeksi Anterior Posterior Axial dan Proyeksi Sedendipity View Shoulder - Rusli, Rini Hatma; Ariyanto, Bambang (An Idea Health Journal, 2024)
This study aims to determine how the results of Analysis of Os Clavicula Radiography Results on Projection of Anterior Posterior Axial and Projection of Serendipity View Shoulder. This research was conducted in Stikes Maluku Husada Radiology Laboratory on July until August 2023, that used observational descriptive by collecting data from respondents who filled question list which in this case used 10 respondents consisting of 5 radiologist and 5 radiographers and other data obtained from study of literature. According to research results, concluded that the results of radiography Os clavicula on Serendipity View Shoulder Projection is better than AP Axial projections based on the value of average obtained for the Serendipity View Shoulder is 3,375 and AP Axial is 2,725.